2022
DOI: 10.1002/ldr.4498
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term manure application enhances organic carbon and nitrogen stocks in Mollisol subsoil

Abstract: Subsoils contain half of the total soil organic carbon (SOC) that is supposed to be relatively more persistent than that present in the topsoil. Improving SOC and total nitrogen (TN) stocks in croplands is crucial to mitigate climate change and ensuring food security. However, our insight into how the management practices and climatic variables influence stocks of SOC and TN, and crop grain yields in the soil profile is limited. In this study, we assessed the long-term impacts of mineral and manure fertilizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 144 publications
3
4
0
Order By: Relevance
“…As expected, there was a gradual decline in TC and TN concentrations. These outcomes are in line with several similar studies (Abrar et al., 2023; Gai et al., 2018; Giacometti et al., 2013). In addition to abundant root biomass, the topsoil has additional aboveground residue input which contributed to the higher TC and TN concentrations in the top layer of soil (Liu, 2005; Wu et al., 2004).…”
Section: Discussionsupporting
confidence: 92%
“…As expected, there was a gradual decline in TC and TN concentrations. These outcomes are in line with several similar studies (Abrar et al., 2023; Gai et al., 2018; Giacometti et al., 2013). In addition to abundant root biomass, the topsoil has additional aboveground residue input which contributed to the higher TC and TN concentrations in the top layer of soil (Liu, 2005; Wu et al., 2004).…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a great difference observed for SOC storage for different soil depths, whereby, the top soil (0-20cm) showed signi cantly highest SOC storage as compared to other depths. This is consistent with Abrar et al ( 2022) who observed the highest SOC storage in top soil layer under long-term fertilization in a Chinese Mollisol [24]. Moreover, the manure combined with NPK had the highest SOC storage along the soil pro le (Fig.…”
Section: Fertilization Impacts On Soc Storage and Sequestrationsupporting
confidence: 91%
“…Kutai, Kranjingan Village, Sumbersari Subdistrict, Jember (8°1202.1"S 113°4340.9"E). Based on data from the Central Statistics Agency, Indonesian (2023), the study site in the Jember region had average humidity and temperature conditions of 80.02% and 27.06°C, respectively, in the year 2022. The duration of sunlight in the Jember region in August, September, October, and November 2022 was 9%, 9%, 20%, 16%, and 26%, respectively.…”
Section: Study Area and Experimental Designmentioning
confidence: 99%